An Image Case of Lepromatous Leprosy in a Patient With Parkinson Disease - Rachel E. Strength; Shirin Mazumder (Annals of Internal Medicine: Clinical Cases)
A 72-year-old man with Parkinson disease presented with 18 months of diffuse blotchiness without associated pain or pruritis. Fite stain and Mycobacterium leprae polymerase chain reaction of a skin biopsy specimen were positive, and he was diagnosed with lepromatous leprosy.